Oxidation and reduction of pig skeletal muscle ryanodine receptors - Haarmann, Claudia S.; Fink, Rainer; Dulhunty, Angela F. (Biophysical journal, 1999)
Time-dependent effects of cysteine modification were compared in skeletal ryanodine receptors (RyRs) from normal pigs and RyRMH (Arg615 to Cys615) from pigs susceptible to malignant hyperthermia, using the oxidizing reagents 4,4′-dithiodipyridine (4,4′-DTDP) and 5,5′-dithio-bis(2-nitrobenzoic acid) (DTNB) or the reducing agent dithiothreitol (DTT). Normal and RyRMH channels responded similarly to all reagents. DTNB (1mM), either cytoplasmic (cis) or luminal (trans), or 1mM 4,4′-DTDP (cis) activated RyRs, introducing an additional long open time constant. 4,4′-DTDP (cis), but not DTNB, inhibited channels after >5min. Activation and inhibition were relieved by DTT (1-10mM). DTT (10mM, cytoplasmic or luminal), without oxidants, activated RyRs, and activation reversed with 1mM DTNB. Control RyR activity was maintained with 1mM DTNB and 10mM DTT present on the same or opposite sides of the bilayer. We suggest that 1) 4,4′-DTDP and DTNB covalently modify RyRs by oxidizing activating or inhibiting thiol groups; 2) a modified thiol depresses mammalian skeletal RyR activity under control conditions; 3) both the activating thiols and the modified thiols, accessible from either cytoplasm or lumen, reside in the transmembrane region; 4) some cardiac sulfhydryls are unavailable in skeletal RyRs; and 5) Cys615 in RyRMH is functionally unimportant in redox cycling.
Gesehen am 27.04.2021